Succinylation modification provides new insights for the treatment of immunocompromised individuals with drug-resistant Aspergillus fumigatus infection - Chen, Xianzhen; Lei, Wenzhi; Meng, Hui; Jiang, Yi; Zhang, Sanli; Chen, Huyan; Du, Mingwei; Xue, Xiaochun (Frontiers in Immunology, 2023)
Invasive Aspergillus fumigatus infection poses a serious threat to global human health, especially to immunocompromised individuals. Currently, triazole drugs are the most commonly used antifungals for aspergillosis. However, owing to the emergence of drug-resistant strains, the effect of triazole drugs is greatly restricted, resulting in a mortality rate as high as 80%. Succinylation, a novel post-translational modification, is attracting increasing interest, although its biological function in triazole resistance remains unclear. In this study, we initiated the screening of lysine succinylation in A. fumigatus. We discovered that some of the succinylation sites differed significantly among strains with unequal itraconazole (ITR) resistance. Bioinformatics analysis showed that the succinylated proteins are involved in a broad range of cellular functions with diverse subcellular localizations, the most notable of which is cell metabolism. Further antifungal sensitivity tests confirmed the synergistic fungicidal effects of dessuccinylase inhibitor nicotinamide (NAM) on ITR-resistant A. fumigatus. In vivo experiments revealed that treatment with NAM alone or in combination with ITR significantly increased the survival of neutropenic mice infected with A. fumigatus. In vitro experiments showed that NAM enhanced the killing effect of THP-1 macrophages on A. fumigatus conidia. Our results suggest that lysine succinylation plays an indispensable role in ITR resistance of A. fumigatus. Dessuccinylase inhibitor NAM alone or in combination with ITR exerted good effects against A. fumigatus infection in terms of synergistic fungicidal effect and enhancing macrophage killing effect. These results provide mechanistic insights that will aid in the treatment of ITR-resistant fungal infections.